2012
DOI: 10.1177/0748233711434957
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exposure to electromagnetic field on rat myocardium

Abstract: Exposure to electromagnetic fields (EMFs) causes increased adverse effects on biological systems. The aim of this study was to investigate the effects of EMF on heart tissue by biochemical and histomorphological evaluations in EMF-exposed adult rats. In this study, 28 male Wistar rats weighing 200-250 g were used. The rats were divided into two groups: sham group (n = 14) and EMF group (n = 14). Rats in sham group were exposed to same conditions as the EMF group except the exposure to EMF. Rats in EMF group we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 18 publications
1
15
0
1
Order By: Relevance
“…The level of GSH can be raised on account of an adaptive response against low intensities oxidative stress owing to an increment in its synthesis; however, strong oxidative stress may depress GSH levels due to the oxidation of GSH to GSSG and the deficiency of the adaptive response skills (Martínez-Sámano et al, 2010). In the several studies, it has been reported that exposures of different intensity and frequency MF can alter the antioxidant conditions of various animals and tissues (Lee at al., 2002;Seyhan and Canseven, 2006;Martínez-Sámano et al, 2010;Kiray et al, 2013). The present study demonstrated that intermittent exposure to 50 Hz, 1.5 mT ELF-MF 4h/day during 7 days increased GSH levels in brain and heart tissues.…”
Section: Discussionsupporting
confidence: 57%
“…The level of GSH can be raised on account of an adaptive response against low intensities oxidative stress owing to an increment in its synthesis; however, strong oxidative stress may depress GSH levels due to the oxidation of GSH to GSSG and the deficiency of the adaptive response skills (Martínez-Sámano et al, 2010). In the several studies, it has been reported that exposures of different intensity and frequency MF can alter the antioxidant conditions of various animals and tissues (Lee at al., 2002;Seyhan and Canseven, 2006;Martínez-Sámano et al, 2010;Kiray et al, 2013). The present study demonstrated that intermittent exposure to 50 Hz, 1.5 mT ELF-MF 4h/day during 7 days increased GSH levels in brain and heart tissues.…”
Section: Discussionsupporting
confidence: 57%
“…Otherwise, it may be worth considering that a magnetic pulse is also constantly generated with each electrical pulse; the heartbeat generates a magnetic field, which is the strongest magnetic field of the human body (100 pT) [ 50 , 51 ]. Also external electromagnetic fields have been shown to markedly affect heart function in experimental animals [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 Recent research has described how EMFs can constitute external sources for the formation of free radicals in blood cells, 37 the brain, 38 spermatozoids, 39 and myocardial tissue. 40 The thyroid gland is by nature an oxidative organ, and when additional oxidative abuse is caused by exogenous pro-oxidants (ionizing radiation would be the most significant), damage to the macromolecules in the gland increases, possibly leading to thyroid pathology or cancer. 41 In spite of this, a direct relation between thyroid cancer and exposure to EMFs has not yet been established.…”
Section: Discussionmentioning
confidence: 99%